Respuestas

  • Usuario de Brainly
2013-12-14T22:28:23+01:00
A). -5x + 4y = -2
       x + y =  -1   ⇒ x = -1 - y

 -5*( -1 - y) + 4y = -2 
5 + 5y + 4y = -2 
9y = -2 - 5
9y = -7
y = -7/9          

x = -1 - y  ⇒ x = -9/9 + 7/9 = -2/9
x = -2/9

b). -4x + 4y  = 7          -40x + 40y = 70         
      10x + 3y = 8   ⇒    40x + 12y = 32   ⇒  52y = 102  ⇒ y = 102/52 = 51/26
y = 51/26

10x + 3y = 8  ⇒ 10x = 8 - 153/26  ⇒ 10x = 208/26 - 153/26  ⇒ 10x = 55/26
x = 55/260


c). -7x - 1/3 = 5x + 7  
      2y + 5/3 = -x  ⇒ x = -2y - 5/3

-7x - 1/3 = 5x + 7  
-12x = 7 + 1/3
-12x = 22/3
-12* (-2y - 5/3) = 22/3
24y + 41/3 = 22/3
24y = 22/3 - 41/3
24y = -19/3
y = (-19/3)/24
y = -19/72

x = -2y - 5/3  ⇒ x = -2* (-19/72) - 5/3  ⇒ x = 38/72 - 5/3  ⇒ x = 19/36 - 5/3  ⇒
x = 19/36 - 60/36  ⇒ x = -41/36